Macrophage polarization in acute myocardial infarction: multidimensional regulation and emerging therapeutic opportunities - Ye, Zilv; Wang, Bo; Wan, Zhengdong; Guo, Jiawei (Frontiers in Immunology, 2026)
Macrophage polarization is a central determinant of the inflammatory response and tissue repair following acute myocardial infarction (AMI). The dynamic transition from a pro-inflammatory M1 phenotype to an anti-inflammatory M2 phenotype is critical for limiting myocardial injury and promoting functional recovery. Recent advances have uncovered complex regulatory mechanisms governing macrophage polarization, including metabolic reprogramming, immune signaling pathways, and alterations within the cardiac microenvironment. Elucidating these processes provides important insights for the development of innovative therapeutic strategies aimed at enhancing cardiac repair. This review summarizes current knowledge on macrophage polarization in AMI, with a particular focus on the multifaceted regulatory networks that modulate the balance between M1 and M2 macrophages. Emerging therapeutic approaches targeting these pathways—such as molecular interventions, gene editing technologies, nanomedicine-based delivery systems, and modulation through traditional Chinese medicine—hold significant promise for improving cardiac repair and preventing adverse remodeling. The integration of these strategies may offer novel opportunities for the clinical management of AMI, ultimately advancing efforts to optimize heart recovery after infarction.